Public Education Recurrent Expenditure and Productivity in the Manufacturing Sector in Niger - Ogunjobi, Festus; Odusanya, Ibrahim; George, Emmanuel (The European Journal of Applied Economics, 2024)
The debate on whether governments should increase their human capital investment is a popular topic within the realm of economics. This research seeks to solve this issue by looking into the importance of productivity in the manufacturing output as well as the function of productive expenditure.The study examines how the recurrent expenditure of public education in Nigeria between 1981 and 2019 affected manufacturing productivity. The study employed the Augmented Dickey-Fuller (ADF) unit root test and Auto Regressive Distributive Lags (ARDL) approach to analyze the relationship between public education recurrent expenditure, public health spending, trade openness, inflation rate, and the output of the manufacturing sector. The study reveals that public education recurrent expenditure is not significantly associated with manufacturing productivity. According to the study, the government should also concentrate on implementing policy frameworks aimed at improving manufacturing sector productivity by targeting public recurrent education spending.